Proverbs of the Arabs and their impact on preference in the interpretation of Al-Nisaburi – A comparative descriptive study – - Mousa, Rana M.Salah Eddin; Asa'ad, Ali Muhammed (Arab Journal for Sciences and Research Publishing, 2021)
This research aims to reveal the Arab proverbs that help us to control the meanings of Quranic words and verses to enrich Quranic meanings and consolidate them in the souls, and to identify a new face of the rhetorical miracle in the Holy Quran, and that it was revealed in the language of the Arabs and their methods of tracking wisdom and communicating with it, and shedding light on Arabic proverbs to be a center for future studies, as Arabic proverbs have not received sufficient attention from researchers so far. Al-Nisaburi’s interest in Arabic proverbs and their use in his interpretation, and his employment in clarifying the meanings of words and Quranic verses, and taking them as a means of weighting, is what distinguished him in his interpretation, and this is what prompted me to search for and study its sources and to find out how Al-Nisaburi used it to clarify the meanings of some words and Quranic verses, and its role in determining its interpretation. In this study, I used the comparative descriptive method, which is based mainly on the use of complete induction of all proverbs contained in the interpretation of Al-Nisaburi, and study it, taking into account the comparison with other commentators, then drawing the overall results that evaluate the work of Al-Nisaburi in employing Arabic proverbs in his interpretation.